Development of pectin nanoparticles through mechanical homogenization for dissolution enhancement of itraconazole - Kanokporn Burapapadh; Hirofumi Takeuchi; Pornsak Sriamornsak (Elsevier, 2016)
A simple method to fabricate itraconazole (ITZ)-loaded pectin nanoparticles prepared from nanoemulsion templates is described in this study. Nanoemulsions containing ITZ were prepared by a mechanical homogenization using pectin as emulsifier. After freeze-drying, the morphology, crystallinity state, thermal properties, drug dissolution and stability of the obtained pectin nanoparticles were characterized. The results demonstrated that the morphology of freeze-dried products was different, depending on the type of internal phase; the nanoparticles prepared from chloroform-based nanoemulsions were completely dried and provided a fragile characteristic. The pectin nanoparticles also demonstrated good properties in terms of redispersibility, thermal properties, drug crystallinity and dissolution. The ITZ-loaded pectin nanoparticles showed high percentage of drug dissolved (about 60-80% within 2 h), and maintained their good dissolution properties even after 1-year storage. The results suggested that freeze-dried pectin nanoparticles prepared from nanoemulsions could be used as an effective carrier for enhancement of ITZ dissolution.